Offshore Aquaculture: I Know It When I See It - Froehlich, Halley E.; Smith, Alexandra; Gentry, Rebecca R.; Halpern, Benjamin S. (Frontiers in Marine Science, 2017)
Offshore aquaculture is increasingly viewed as a mechanism to meet growing protein demand for seafood, while minimizing adverse consequences on the environment and other uses in the oceans. However, despite growing interest in offshore aquaculture, there appears to be no consensus as to what measures commonly define an offshore site or how effects of offshore aquaculture – relative to more nearshore practices – are assessed. This lack of agreement on what constitutes offshore aquaculture has the potential to convolute communication, create uncertainty in regulatory processes, and impede understanding of the ecological implications of offshore farming. To begin addressing these issues, we reviewed and analyzed biologically-focused primary and gray literature (Ntotal = 70) that categorize and quantify characteristics of offshore aquaculture from around the world. We found that many ‘offshore’ descriptions are relatively close to shore (< 3 nm) and significantly shallower (minimum depth ≤ 30 m) than may be assumed. We also uncovered an overall lack of consistent reporting of even the most common location-focused metrics (distance from shore, depth, current), a dearth of impact related studies (n = 17), and narrow scope of the studies themselves (i.e., 82% nutrient pollution). Of the finite subset of articles that investigated negative ecological impacts of offshore aquaculture, we found the probability of any measurable impact from an offshore farm appears to significantly decrease with distance from the farm (probability of measurable response at 90 m ± SE = 0.01 ± 0.03). Such general, but informative points of reference could be more robustly quantified with better systematic and standardized reporting of physical farm characteristics and a broader scope of ecological investigation into the effects of marine aquaculture. With offshore aquaculture still in its infancy, consistent metrics are needed for a comparable framework to guide sustainable offshore aquaculture research and development globally.